A rare complication of DRESS syndrome in the treatment of cardiac device-related lead thrombus and infective endocarditis - James Tomlinson; Anil Gurung; Oliver Watkinson (Clinical Medicine)
Case presentation: A 65-year-old man collapsed in a pub after consuming 8 pints of beer. His medical history included recent antibiotics for a chest infection, ischaemic heart disease, dual-chamber permanent pacemaker, chronic obstructive pulmonary disease, hypertension, insulin-dependent diabetes mellitus, peripheral vascular disease and haemorrhagic pancreatitis.Clinical examination showed no peripheral stigmata of infective endocarditis (IE) or heart failure. Inflammatory markers were raised and troponin elevated at 323 ng/L. Chest X-ray was clear. Electrocardiography (ECG) showed sinus rhythm and no ischaemic changes. Emergency device check confirmed normal pacing function and no underlying arrhythmias.He was treated with antibiotics for infection of unknown origin and managed for type 2 myocardial infarction secondary to collapse and hypoxia. CTPA suggested mass formation around the pacing lead concerning for IE or thrombus formation. Antibiotics were altered to empirical treatment for cardiac device-related IE with vancomycin, gentamicin and rifampicin.Transthoracic and transoesophageal echocardiography showed large, irregular, echogenic, mobile masses attached to the ventricular pacing lead within the right atrium, suggestive of vegetations in the clinical context (Fig 1). PET-CT demonstrated multiple new infective lung nodules and no increased tracer uptake around the pacing leads to suggest IE.He was discussed at the regional complex heart rhythm team meeting, with recommendations for at least 6 weeks of antibiotic therapy, oral anticoagulation for possible pacing lead thrombus and device extraction. Approximately 10 days after starting rivaroxaban, he developed a widespread macular rash, high fevers and mild peripheral blood eosinophilia consistent with drug reaction with eosinophilia and systemic symptoms (DRESS). He deteriorated further with evolving multi-organ failure.Post-mortem (PM) examination confirmed non-infective thrombus associated with the pacing lead, measuring 5 mm in thickness and 4 cm in length. Evidence of an allergic reaction was supported by findings of dermatitis, both clinically and histologically, markedly elevated PM mast cell tryptase concentrations, and atypical lymphocytosis seen in several organs. Discussion: DRESS is a rare, serious adverse drug reaction (ADR) marked by an extensive morbilliform rash, involvement of visceral organs, generalised lymphadenopathy, eosinophilia and atypical lymphocytes.1 DRESS is part of a spectrum of severe cutaneous ADRs, presenting with facial oedema and, in extreme cases, severe oral mucositis, indicative of a DRESS/Stevens-Johnson syndrome overlap.2,3The clinical presentation is heterogenous. Despite stopping the offending drug, disease flares may persist and the disease course is typically prolonged between 2 and 8 weeks.4 Several medications have been widely implicated in the aetiology of DRESS, including vancomycin and B-lactam antibiotics, with onset of symptoms varying between 12 days and 4 weeks.5,6 Antibiotics, anticonvulsants (particularly phenytoin) and sulfonamides are the most common offending agents.7,8The prevalence of intracardiac thrombi on transvenous leads from cardiac implantable devices varies widely, ranging from 1.4% to 30%.9 Most of these thrombi are found incidentally during lead extraction or on intracardiac echocardiography during ablation procedures.9 Anticoagulation therapy is the mainstay of treatment for most intracardiac pacemaker lead thrombus, although thrombolytics and/or thrombectomy is occasionally required in acute or subacute cases of venous occlusion. Serial imaging is required to assess for thrombus resolution and lead extraction is generally recommended in cases that fail to respond.10